Manajemen Pembiayaan Modal Kerja Bagi Pelaku Usaha di BMT Hasanah Ponorogo - Vidyawati, Sefia (CV. Civiliza Publishing, 2024)
Introduction/Main Objectives: This research aims to determine the management and impacts resulting from working capital financing management at BMT Hasanah Ponorogo. Research Methods: The method used in this research is field research with a qualitative approach. The data collection uses triangulation techniques, interviews, observation, and documentation. Finding/Results: The study's results indicate that the management of working capital financing at BMT Hasanah Ponorogo is quite good because it has gone through an excellent planning, organizing, controlling, and monitoring process. However, paying attention to caution and accuracy in financing customers is still necessary. Conclusion: Good working capital financing management will have an impact on the profits obtained by the bank. This will also increase customer trust to transact at BMT Hasanah Ponorogo.